2016
DOI: 10.1111/jam.13338
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination ofClostridium difficilein food and the environment: Significant sources ofC. difficilecommunity-acquired infection?

Abstract: Summary Clostridium difficile is a significant pathogen with over 300 000 cases reported in North America annually. Previously, it was thought that C. difficile was primarily a clinically associated infection. However, through the use of whole genome sequencing it has been revealed that the majority of cases are community acquired. The source of community‐acquired C. difficile infections (CDI) is open to debate with foodborne being one route considered. Clostridium difficile fits the criteria of a foodborne pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 98 publications
5
61
0
Order By: Relevance
“…; Warriner et al . ). Secondly, some strains were given internal nomenclature (QX types) because they did not correspond to any internationally recognized ribotypes in our library collection.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Warriner et al . ). Secondly, some strains were given internal nomenclature (QX types) because they did not correspond to any internationally recognized ribotypes in our library collection.…”
Section: Discussionmentioning
confidence: 97%
“…The concentration of C. difficile spores on contaminated foods is generally presumed to be low, with studies that report positive samples detecting C. difficile by enrichment culture only (Weese et al 2010b) or, if positive by direct culture, counts of 20-240 spores per g (Weese et al 2009). The infective dose of C. difficile is currently unknown, although suggestion has been made that it could be low (100-1000 spores) depending on host susceptibility (Hensgens et al 2012;Warriner et al 2017). Secondly, some strains were given internal nomenclature (QX types) because they did not correspond to any internationally recognized ribotypes in our library collection.…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiology of gastrointestinal disease caused by C. difficile is slowly being elucidated internationally. Studies have demonstrated similarities between C. difficile isolates from animals or foods with clinical isolates, suggesting zoonotic transmission (Janezic et al ; Knetsch et al ; Knight and Riley ; Warriner et al ). The formation of spores by C. difficile provides significant potential for wide dissemination, and environmental contamination of foods through water and irrigation systems may be important routes for transmission of infection (Zidaric et al ; Romano et al ; Xu et al ).…”
Section: Introductionmentioning
confidence: 99%
“…() found that it can tolerate O 2 concentrations below 1% and they found that SigB contributes directly to oxygen‐mediated stress tolerance by regulating genes that are known to be involved in O 2 detoxification in other anaerobes. This is, from a physiological point of view, a rather notable finding since the SigB‐mediated general stress response system has so far only been studied in any level of detail in aerobic microbes (Hecker et al ., ; Guldimann et al ., ). (ii) C. difficile can form highly stress‐ and desiccation‐resistant endospores (Fimlaid and Shen, ; Bhattacharjee et al ., ) and the fecal/oral route of these metabolically dormant entities is an important way for the dissemination of this pathogen and for the overall infection and intestine colonization process (Shen, ; Abt et al ., ; Warriner et al ., ). Kint et al .…”
mentioning
confidence: 97%
“…This is, from a physiological point of view, a rather notable finding since the SigB-mediated general stress response system has so far only been studied in any level of detail in aerobic microbes (Hecker et al, 2007;Guldimann et al, 2016). (ii) C. difficile can form highly stress-and desiccationresistant endospores (Fimlaid and Shen, 2015;Bhattacharjee et al, 2016) and the fecal/oral route of these metabolically dormant entities is an important way for the dissemination of this pathogen and for the overall infection and intestine colonization process (Shen, 2015;Abt et al, 2016;Warriner et al, 2017). Kint et al (2017) found that more than 200 genes encoding proteins involved in different stages of the sporulation process were differentially expressed in the sigB 1 /sigB pair of C. difficile strains.…”
mentioning
confidence: 99%